Revisiting the Causes of the Pull-to-Centre Effect: Evidence From China - Yang, Lushuang; Cai, Dahai (Frontiers in Psychology, 2022)
Prior experimental studies have shown that individuals' actual ordering decisions significantly deviate from the theoretical optimum in newsvendor problems and show the robust pull-to-centre (PTC) effect. Several human behaviours have been confirmed to be the causes of the PTC. However, most newsvendor experiments have been conducted in multicultural countries (e.g., the United States and Germany). As there exist mutual influences between culture and behaviour, in this study, we revisit the ordering biases in a monocultural country to examine the robustness of the PTC and whether the causes can still explain this phenomenon. Our results show that the PTC still prevails, and heuristics still work. However, overconfidence cannot perfectly interpret the PTC in China for probable inconsistent confidence levels in individual judgements and decisions. Moreover, the "centre" may no longer be the mean demand but the average value of the realised demand. We explain these changes from the perspective of cultural differences. To be more specific, collectivism, holistic style, and Doctrine of the Mean play vital roles in Chinese newsvendors' decisions.